2017
DOI: 10.3390/ijerph14040369
|View full text |Cite
|
Sign up to set email alerts
|

Time Trend and Demographic and Geographic Disparities in Childhood Obesity Prevalence in China—Evidence from Twenty Years of Longitudinal Data

Abstract: Childhood overweight and obesity (ow/ob) has become a serious threat to many countries, including China. However, limited evidence was obtained from longitudinal data in China. This study examined the secular trends and geographic variation in the prevalence of ow/ob and obesity only, and age, gender, and urban-rural disparities among school-aged children across China. Data from children aged 6–17 surveyed in China Health and Nutrition Survey (CHNS) from 1991 (n = 2712) to 2011 (n = 1054) were used. Overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 22 publications
4
59
0
Order By: Relevance
“…In addition, we found that only rural children and recent cohorts had a high BMI increase from self‐perception as fat compared with urban children and the previous cohort after adjusting for demographic covariates. In 2011, childhood obesity was about 1.5 times more prevalent in urban than rural areas in China . Rural people may not view obesity negatively, and therefore they do not react promptly to fatness after perceiving it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we found that only rural children and recent cohorts had a high BMI increase from self‐perception as fat compared with urban children and the previous cohort after adjusting for demographic covariates. In 2011, childhood obesity was about 1.5 times more prevalent in urban than rural areas in China . Rural people may not view obesity negatively, and therefore they do not react promptly to fatness after perceiving it.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that only rural children and recent cohorts had a high BMI increase from self-perception as fat compared with urban children and the previous cohort after adjusting for demographic covariates. In 2011, childhood obesity was about 1.5 times more prevalent in urban than rural areas in China (40). Rural people may not view Children's self-ratings using nine silhouettes for (1) which one was most like them and (2) which one they would most like to look like were grouped into the following three levels: thin (silhouettes 1-3), average (silhouettes 4-6), and fat (silhouettes 7-9).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the prevalence of both adult and childhood obesity in China has sharply increased in recent years. The China Health and Nutrition Survey (CHNS) reported that the prevalence of childhood (6-17 years) obesity had risen from 2.8% in 1991 to 10.1% in 2011 [4].…”
Section: Introductionmentioning
confidence: 99%
“…The rise of obesity prevalence has been observed in China [32], which may be attributed to environmental factors. However, limited previous efforts have focused on environmental risk factors for obesity in China.…”
Section: Discussionmentioning
confidence: 99%